A Study of the Pollution of Heavy Metal of Discharged Water from the South Baghdad Thermal Power Station - Saud Salman Mohammed (Journal of Global Pharma Technology, 2018)
The present study was conducted to demonstrate the effect of the Thermal power station on the concentration of heavy metals (Fe, Pb, Ni, Cu, Cr, Cd, As, Se) from January 2017 to August 2017. The concentrations of the heavy elements under study were estimated by atomic absorption spectroscopy. The mean concentrations of heavy metals (Fe, Pb, Ni, Cu, Cr, Cd, As, Se) respectively in the industrial water discharged to the Tigris River were measured in mg/l (2.35, 0.266, 0.318, 0.314, 0.093, 0.117, 0.024 and 0.359). The results of the study recorded contamination of the soil of the study area with heavy elements (Pb 89.25 mg / l), (Cd 8.41 mg / l) and (Ni 93.75 mg / l). The study concluded that the power station affected the pollution of ecosystems and deteriorated the quality of the Tigris River in the southern part of Baghdad.                              Keywords:  Heavy metals, Thermal power station, Atomic absorption spectroscopy.